School-Related Determinants of School Completion in Public Primary Schools in Kenya: A Case of Kajiado North Sub-County, Kajiado County, Kenya - Kang’aru , Mary W.; Kimosop , Maurice; Mbugua , Zachariah K. (African Journal of Education,Science and Technology (AJEST), 2018)
The rapid increase in enrolment in public primary schools has strained the facilities, resulting in low standards of sanitation and inadequate physical resources due to the rising population of pupils. The supply of drinking water to pupils is of questionable quality and has been indicated as a possible causal factor to escalating incidences of sickness among children. The combined effect of these factors has been, inconsistent school attendance, low school completion and in extreme cases dropout from school. This situation has presented challenges in relation to learners’ school completion of the primary school cycle. This study sought to find out school related determinants of school completion among pupils in public primary schools in Kajiado North Sub-County, Kenya. Therefore the aim of this study was to evaluate the influence of sanitation facilities on dropout among pupils and identify physical resources influences on dropout among pupils in public primary schools in Kajiado North Sub-County in Kenya. Descriptive survey research design informed by the persistence, progression, retention, completion model as advanced by Levitz and Noel was used. The target population of this study consisted of 93 head teachers, 701 teachers in the 93 primary schools in five (5) educational zones in Kajiado North Sub-County. The study applied stratified random sampling technique to select the respondents to be included in this study. The sample size was determined using Gay’s principle which yielded a sample of 141 teachers and 19 head teachers. Questionnaires were used to collect the data. Collected data was analysed using descriptive statistics using Statistical Package for Social Sciences (SPSS). The study established that sanitation facilities and school infrastructure contributed to pupil school dropout among pupils in public primary schools in the Sub-County. From the findings it can be concluded that the school-based factors were significant influences of educational dropout and should be put into account while dealing with wastage. Schools should have adequate sanitation and teaching learning facilities in order to actualize pupil completion in primary schools. These findings enhanced the understanding that school-based factors influenced wastage in public primary schools in Kajiado Sub-County